Trimethylamine-N-oxide is associated with cardiovascular mortality and vascular brain lesions in patients with atrial fibrillation. Issue 5 (2nd January 2023) - Luciani, Marco; Müller, Daniel; Vanetta, Chiara; Diteepeng, Thamonwan; von Eckardstein, Arnold; Aeschbacher, Stefanie; Rodondi, Nicolas; Moschovitis, Giorgio; Reichlin, Tobias; Sinnecker, Tim; Wuerfel, Jens; Bonati, Leo H; et al.
Abstract : Objective: Trimethylamine-N-oxide (TMAO) is a metabolite derived from the microbial processing of dietary phosphatidylcholine and carnitine and the subsequent hepatic oxidation. Due to its prothrombotic and inflammatory mechanisms, we aimed to assess its role in the prediction of adverse events in a susceptible population, namely patients with atrial fibrillation. Methods: Baseline TMAO plasma levels were measured by liquid chromatography-tandem mass spectrometry in 2379 subjects from the ongoing Swiss Atrial Fibrillation cohort. 1722 underwent brain MRI at baseline. Participants were prospectively followed for 4 years (Q1–Q3: 3.0–5.0) and stratified into baseline TMAO tertiles. Cox proportional hazards and linear and logistic mixed effect models were employed adjusting for risk factors. Results: Subjects in the highest TMAO tertile were older (75.4±8.1 vs 70.6±8.5 years, p<0.01), had poorer renal function (median glomerular filtration rate: 49.0 mL/min/1.73 m 2 (35.6–62.5) vs 67.3 mL/min/1.73 m 2 (57.8–78.9), p<0.01), were more likely to have diabetes (26.9% vs 9.1%, p<0.01) and had a higher prevalence of heart failure (37.9% vs 15.8%, p<0.01) compared with patients in the lowest tertile. Oral anticoagulants were taken by 89.1%, 94.0% and 88.2% of participants, respectively (from high to low tertiles). Cox models, adjusting for baseline covariates, showed increased total mortality (HR 1.65, 95% CI 1.17 to 2.32, p<0.01) as well as cardiovascular mortality (HR 1.86, 95% CI 1.21 to 2.88, p<0.01) in the highest compared with the lowest tertile. When present, subjects in the highest tertile had more voluminous, large, non-cortical and cortical infarcts on MRI (log-transformed volumes; exponentiated estimate 1.89, 95% CI 1.11 to 3.21, p=0.02) and a higher chance of small non-cortical infarcts (OR 1.61, 95% CI 1.16 to 2.22, p<0.01). Conclusions: High levels of TMAO are associated with increased risk of cardiovascular mortality and cerebral infarction in patients with atrial fibrillation. Trial registration number: NCT02105844 .